The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00267-009-9314-8
|View full text |Cite
|
Sign up to set email alerts
|

Erosional Consequence of Saltcedar Control

Abstract: Removal of nonnative riparian trees is accelerating to conserve water and improve habitat for native species. Widespread control of dominant species, however, can lead to unintended erosion. Helicopter herbicide application in 2003 along a 12-km reach of the Rio Puerco, New Mexico, eliminated the target invasive species saltcedar (Tamarix spp.), which dominated the floodplain, as well as the native species sandbar willow (Salix exigua Nuttall), which occurred as a fringe along the channel. Herbicide applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 40 publications
2
52
0
Order By: Relevance
“…Willow may be an important indicator of overall riparian health for some systems (Booth et al 2012). Willows help reduce stream temperatures (Zoellick 2004;White and Rahel 2008) and protect stream banks against erosion (Vincent et al 2009). The strong increase in willow cover observed in this study suggests that riparian systems at Hart Mountain are more stable, provide better habitat for many species, and are more resistant to erosion than when cattle were present.…”
Section: Discussionmentioning
confidence: 99%
“…Willow may be an important indicator of overall riparian health for some systems (Booth et al 2012). Willows help reduce stream temperatures (Zoellick 2004;White and Rahel 2008) and protect stream banks against erosion (Vincent et al 2009). The strong increase in willow cover observed in this study suggests that riparian systems at Hart Mountain are more stable, provide better habitat for many species, and are more resistant to erosion than when cattle were present.…”
Section: Discussionmentioning
confidence: 99%
“…The data obtained by the dendrogeomorphic analyses show that in the absence of channel-resetting floods (i.e., >10 yr recurrence interval), control of vegetation during low-flow periods may prevent the stabilization of near-channel surfaces until floods of a sufficient magnitude and duration erode the accumulated channel sediments. Other studies (Pollen-Bankhead et al, 2009;Vincent et al, 2009) have shown that vegetation removal is a feasible mechanism to promote bank destabilization and channel widening. Although management efforts are focused on the promotion of bank destabilization, and limiting the rate and magnitude of channel narrowing, it must also be noted that other associated environmental effects of erosion, such as salt and contaminant transport, are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Tamarix is now the third most common woody plant in western US riparian areas (Friedman et al 2005), and is considered a noxious weed in most states west of the Mississippi River. Tamarisk dominance has led to alterations of riparian ecosystems including soil salinization, local reduction in water resources via excess transpiration (Sala et al 1996;Dahm et al 2002), changing erosion and sedimentation regimes (Graf 1978;Vincent et al 2009), and increasing the susceptibility of riparian areas to wildfire (Busch and Smith 1993;Dudley et al 2011) although the environmental impact of some of these factors has been questioned (Sogge et al 2008;Hultine et al 2010). Tamarix spp.…”
Section: Tamarix Biocontrol Program Historymentioning
confidence: 98%